Pediatric Genitourinary Oncology - Francisco Tibor Dénes; Ricardo Jordão Duarte; Lilian Maria Cristofani; Roberto Iglesias Lopes (Frontiers in Pediatrics, 2013)
Tumours of kidney, bladder, prostate, testis and adrenal represent a large part of the adult urologic practice, but are relatively infrequent in children. The natural history and management of these tumours in the pediatric age is different from that of adults. As result of the successful work of several clinical trial groups in recent decades, there has been a significant improvement in their cure rates. The aim of this article is to review their most significant clinical aspects, as well as to present an update in their management.